Stress during the COVID-19 pandemic moderates pain perception and momentary oxytocin levels - Schneider, Ekaterina; Hopf, Dora; Eckstein, Monika; Scheele, Dirk; Aguilar-Raab, Corina; Herpertz, Sabine; Grinevich, Valéry; Ditzen, Beate (Journal of Clinical Medicine, 2023)
Self-reported pain levels have been associated with increased stress levels during the COVID-19 pandemic. Less is known about the long-term effects of stress on individuals’ physical and emotional pain levels and their associations with the neuropeptide hormone oxytocin. We aimed to predict momentary pain through individual stress levels and momentary oxytocin levels at genuinely high-stress phases, namely during COVID-related lockdowns. In a cross-sectional (n = 254) and a longitudinal (n = 196) assessment during lockdowns in Germany, participants completed a 2-day ecological momentary assessment (EMA) protocol (collecting six saliva samples on two consecutive days each and simultaneously reporting on stress, physical, and emotional pain levels) in 2020, as well as one year later, in 2021. Hierarchical linear modeling revealed significant positive associations between individuals’ stress levels and physical pain, both cross-sectionally (b = 0.017; t(103) = 3.345; p = 0.001) and longitudinally (b = 0.009; t(110) = 2.025; p = 0.045). Similarly, subjective stress ratings showed significant positive associations with emotional pain on a within-person (b = 0.014; t(63) = 3.594; p < 0.001) as well as on a between-person (b = 0.026; t(122) = 5.191; p < 0.001) level. Participants further displayed significantly lower salivary oxytocin when experiencing higher levels of emotional pain (b = −0.120; t(163) = −2.493; p = 0.014). In addition, high-stress levels significantly moderated the association between physical pain and salivary oxytocin (b = −0.012; t(32) = −2.150; p = 0.039). Based on mechanistic and experimental research, oxytocinergic mechanisms have long been suggested to modulate pain experiences, however, this has not yet been investigated in everyday life. Our data, which was collected from a large sample experiencing continued stress, in this case, during the COVID-19 pandemic, suggests that individuals experience more intense physical pain and elevated stress levels, as shown by particularly low salivary oxytocin concentrations.
Gesehen am 20.04.2023